透過線上學習社群發展協作學習和知識建構 Fostering Collaborative Learning and Knowledge Building through Online Learning Communities - Allan H. K. Yuen (Jiàoyù zīliào yǔ túshūguǎn xué, 2004)
面對知識型社會的需求，教育需要培育有能力創造新知識及從中獲益的人材。但是，怎樣的教育才能為學生的終身學習作好準備，實在是重要的課題。近年的教育改革中，課程革新已成為推動改革的重要策略。本文的目的是要通過一個課程革新的個案研究，展示網上學習社群如何幫助小學生作知識建構，裝備自已迎接日後終身的挑戰。我們認為學校能為學生終身學習提供的最好準備，是幫助他們建立一種能理解、創造和改進知識，並與知識一起工作的文化。六間香港小學體會到這種新學習文化的重要，便一同參與利用網上學習社群的方法對科學作專題研習。根據學生和教師的訪談分析，發現他們對網上學習社群的經驗可以歸納成兩個要素:協作學習和知識建構。 To address the demand of knowledge society, the question is what kind of schooling would be best to prepare students for life in the knowledge society. Curriculum innovations have been regarded as an essential strategy for educational reform throughout the era of educational change over the past years. The aim of this paper is to present a case study of curriculum innovation through online learning communities to prepare primary students for lifelong challenges. We argue the best preparation schools can provide for life is to help students build a culture of understanding, creating, improving and working with knowledge. Realizing the impact of such new learning culture, six primary schools in Hong Kong participated in the implementation of online learning communities through science project works. Through the analysis of the interviews of students and teachers, experiences arising from online learning communities were emerged in two major themes, namely, collaborative learning and knowledge.